A nano-reinforced high-strength and high-toughness low-carbon steel and its preparation method

Through nanostrengthening technology, high-temperature uniformization treatment, two-stage forging, staged cooling and short-term isothermal processes were used to prepare high-strength and high-toughness low-carbon steel, which solved the problem of insufficient strength of existing low-carbon steels and achieved strength improvement and performance maintenance.

CN114918362BActive Publication Date: 2025-03-04SHAANXI ZHONGRUI TIANCHENG CONSTRUCTION ENGINEERING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111521799.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-13
Publication Date
2025-03-04
Estimated Expiration
2041-12-13

AI Technical Summary

Technical Problem

The existing low-carbon steel has low strength and is difficult to meet the needs of lightweight and high-performance steel for automobiles.

Method used

Through nanostrengthening technology, nanoscale carbides supplemented by single-phase ferrite and (Ti,Mo)C are prepared by using high-temperature homogenization treatment, two-stage forging, staged cooling and short-term isothermal processes.

Benefits of technology

The strength of low-carbon steel is significantly improved, and the tensile strength increases by 1 to 2 times, while maintaining its good plasticity, toughness and moldability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114918362B_ABST
    Figure CN114918362B_ABST
Patent Text Reader

Abstract

The present invention discloses a nano-reinforced high-strength and high-toughness low-carbon steel and a preparation method thereof, the method comprising the following steps: (1) high-temperature homogenization treatment: heating the steel ingot blank to 1200-1280°C in an inert gas environment to dissolve all carbides and obtain a uniform single-phase austenite structure; (2) two-stage forging: recrystallization zone forging: taking the steel ingot sample out of the atmosphere protection furnace for forging, ensuring that the forging temperature interval is located in the austenite recrystallization zone, and the forging ratio is 60-80%; amorphous zone forging: continuing forging after the recrystallization zone forging is completed, ensuring that the forging temperature interval is located in the austenite amorphous zone, and the forging ratio is 40-60%; (3) staged cooling; (4) short-term isothermal; (5) furnace cooling. The strength of the nano-reinforced high-strength and high-toughness low-carbon steel prepared by the method of the present invention is more than 1-2 times that of the general low-carbon steel, and its good plasticity, toughness and formability are maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-strength and high-toughness low-carbon steel, and in particular to a nano-reinforced high-strength and high-toughness low-carbon steel and a preparation method thereof. Background Art

[0002] Low-carbon and ultra-low-carbon steels not only have low carbon content (usually below 0.1% by mass), but also low alloying element content, simple preparation process, and significant cost advantages. At the same time, (ultra) low-carbon steel has good plasticity, toughness and formability, and is easy to process by cold rolling, hot rolling, stamping, welding and other processing techniques. It is widely used in vehicles, ships, bridges, buildings, machinery, oil and gas pipelines, aviation and other fields. For example, in vehicle engineering, (ultra) low-carbon steel can be used in large quantities to manufacture body structural parts, stampings, door panels, reinforcements, anti-collision devices and suspension components. Commonly used (ultra) low-carbon steels, such as IF steel and calm steel, have good plasticity and formability, with an elongation of more than 30% and a certain strength.

[0003] However, under normal circumstances, (ultra) low carbon steel has low strength, with a yield strength of about 200-300 MPa and a tensile strength of about 300-400 MPa. With the development of lightweight automobiles and the increasing demand for high-performance structural steel, higher requirements are placed on the strength of (ultra) low carbon steel.

[0004] By increasing the carbon content and alloy content in steel, the strength of the steel can be effectively increased, but its plasticity, toughness and formability will be significantly reduced, which is not conducive to the improvement of overall performance and also leads to increased costs. On the other hand, by changing the microstructure and preparing dual-phase steel or complex-phase steel, the strength can also be improved, but the process is more complicated. Moreover, during the deformation process of dual-phase or complex-phase structures, the coordination between hard and soft tissues is insufficient, which easily leads to stress concentration and the formation of microscopic defects such as micropores, resulting in toughness and formability that do not meet the requirements. Summary of the invention

[0005] The purpose of the present invention is to provide a nano-reinforced high-strength and high-toughness low-carbon steel and a preparation method thereof, which solves the problem of low strength of existing low-carbon steel. The strength of the nano-reinforced high-strength and high-toughness low-carbon steel is increased by more than 1 to 2 times that of general low-carbon steel, and its good plasticity, toughness and formability are maintained.

[0006] In order to achieve the above object, the present invention provides a method for preparing nano-reinforced high-strength and high-toughness low-carbon steel, the method comprising the following steps:

[0007] (1) High temperature homogenization treatment

[0008] The steel ingot billet after secondary vacuum melting is heated to 1200-1280° C. in an inert gas environment to dissolve all carbides and obtain a uniform single-phase austenite structure; wherein the steel ingot billet contains the following chemical components in mass percentage: C: 0.03-0.1%, Mn: 1.5-2.5%, Si: 0.15-0.25%, Mo: 0.2-0.4%, Ti: 0.1-0.2%, Al: 0.05-0.1%, and the rest is Fe element, and the mass ratio of Mo to Ti is 2:1;

[0009] (2) Two-stage forging

[0010] Recrystallization zone forging: The ingot sample is taken out from the atmosphere protection furnace for forging. The initial forging temperature is 1200℃±50 and the final forging temperature is T 再 , T 再 is the recrystallization temperature, ensuring that the forging temperature range is in the austenite recrystallization zone, and the forging ratio is 60-80%, so that the deformed grains are recrystallized to form uniform and fine equiaxed grains and refine the austenite grains;

[0011] Forging in amorphous zone: Continue forging after forging in recrystallization zone is completed, and the initial forging temperature is T 始 , T 始 T 再 ±30, the final forging temperature is Ar3 temperature (indicates the starting temperature of austenite transformation into ferrite during cooling), ensuring that the forging temperature range is in the austenite non-crystallization zone, and the forging ratio is 40-60%, so that the grains are not easy to recrystallize, but form dislocation entanglement, promote ferrite nucleation, and inhibit the precipitation of large-particle carbides;

[0012] (3) Staged cooling

[0013] After the two-stage forging is completed, the steel ingot sample is spray-cooled at a cooling rate of about 20 to 30°C / s until the temperature drops to 550 to 650°C, and the cooling is stopped;

[0014] (4) Short-time isothermal

[0015] After the staged cooling, the steel ingot sample is placed in a furnace for heat preservation treatment at a temperature of 600-650° C. for a time of 30-90 min, so that austenite is transformed into ferrite and nano-scale carbides mainly composed of (Ti, Mo) C are precipitated near the austenite / ferrite grain boundary;

[0016] (5) Cooling with the furnace

[0017] After the short-time isothermal treatment, the steel ingot sample is air-cooled in the furnace. When the ingot sample is cooled to below 300° C., it is taken out of the furnace and air-cooled to room temperature to obtain nano-reinforced high-strength and high-toughness low-carbon steel.

[0018] The steel ingot blank used in the present invention has the contents of various elements in its components controlled within a certain range, the mass percentage of the C element is 0.03-0.1%, low carbon is maintained, single-phase ferrite is formed, and toughness and formability are improved; the mass percentage of the Mn element is 1.5-2.5%, which can reduce the Ar3 temperature, hinder the growth of carbide particles, and improve the strengthening effect; the mass ratio of the Si element is 0.15-0.25%, Si is dissolved in the ferrite matrix, solid solution strengthening effect is generated, and toughness is improved; the mass percentage of the Al element is 0.05-0.1%, which is a deoxidizing element, fixes the N element, and improves the purity of the metal; the mass percentage of the Mo element is 0.2-0.4%, which can inhibit the formation of pearlite and prevent the formation of large-particle carbides at the grain boundary; the mass percentage of the Ti element is 0.1-0.2%, the mass ratio of the Ti element to the Mo element is maintained at 1:2, nanometer-scale carbides mainly composed of (Ti, Mo) C are formed, precipitation strengthening effect is generated, and the best strength and toughness combination is obtained.

[0019] Moreover, the present invention adopts two-stage forging: (1) the first stage is recrystallization zone forging, and its forging temperature range can make the austenite grains recover and recrystallize immediately after deformation, forming uniform and fine equiaxed crystals, refining the austenite grains, and preparing the organization for the next step of refining the ferrite grains. At the same time, in this forging temperature range, after the deformed grains recrystallize, the stress and strain are released, and the strain-induced carbide precipitation is suppressed, which can prevent the occurrence of large-particle carbides; (2) the second stage is non-crystallization zone forging, and its forging temperature is In the forging temperature range, the final forging temperature is Ar3 temperature, which is the ferrite nucleation zone. In this forging temperature range, the recrystallization of austenite is suppressed, deformation can be accumulated in the austenite grains, and the grains are further refined. At the same time, forging in this temperature zone can form a certain amount of dislocation entanglement, which promotes ferrite nucleation and prepares for the subsequent refinement of ferrite grains. On the other hand, dislocation entanglement inhibits the precipitation of carbides in austenite, increases the supersaturation of austenite, and can form supersaturated ferrite in the subsequent process, which is conducive to the precipitation of nano-carbides in ferrite. Therefore, through the two-stage forging process, the austenite grains can be refined to the maximum extent, forming a fine grain strengthening effect, preparing for the subsequent acquisition of fine and uniform ferrite equiaxed crystals; at the same time, this process can inhibit the precipitation of large-particle carbides in austenite, promote the precipitation of nano-scale carbides, and prepare for the subsequent formation of a large number of dispersed carbides. Since the sample continues to cool down during the two-stage forging process, the forging process must be rapid and completed within the predetermined temperature range.

[0020] In addition, the present invention promotes the transformation of austenite into ferrite through a short-time isothermal process, and precipitates a large amount of carbides mainly composed of (Ti, Mo) C near the austenite / ferrite grain boundary, which are dispersedly distributed at the nanometer scale; the isothermal parameters have a significant influence on the type, quantity, size and distribution of the precipitated carbides. In order to ensure the formation of a large amount of dispersedly distributed (Ti, Mo) C nanometer-scale carbides, enhance the precipitation strengthening effect, and ensure that the ferrite grains remain small-sized equiaxed crystals, the holding temperature and time must be strictly controlled. If the temperature is too high and the time is too long, the structure will be coarsened; if the holding temperature is low and the time is short, the ferrite transformation is insufficient and the amount of carbide precipitation is low; in both cases, it is not conducive to improving the strength of the sample.

[0021] Normally, carbides precipitate from three stages. Carbides precipitated in austenite are coarse and should be avoided as much as possible; carbides precipitated in supersaturated ferrite are easy to grow and unevenly distributed, so they should be avoided as much as possible. The present invention adopts a short-time isothermal process and utilizes the principle of phase transformation to precipitate a large amount of carbides near the austenite / ferrite interface, which are nanoscale and evenly dispersed, can produce a significant precipitation strengthening effect, improve strength and maintain good plasticity, toughness and formability.

[0022] Preferably, the T 再 It is 940~960℃.

[0023] Preferably, in the high-temperature homogenization treatment, the holding time is 60 to 90 minutes.

[0024] Preferably, during the forging of the non-crystallized zone, the Ar3 temperature is 750-800°C.

[0025] Preferably, the staged cooling is performed by lowering the temperature to 600-650° C. and then stopping the cooling.

[0026] Preferably, the steel ingot contains the following chemical components in mass percentage: C: 0.03-0.09%, Mn: 1.5-2.3%, Si: 0.15-0.24%, Mo: 0.2-0.4%, Ti: 0.1-0.2%, Al: 0.05-0.08%, and the rest is Fe element.

[0027] Another object of the present invention is to provide a nano-reinforced high-strength and high-toughness low-carbon steel obtained by the preparation method.

[0028] The nano-reinforced high-strength and high-toughness low-carbon steel and the preparation method thereof of the present invention solve the problem of low strength of existing low-carbon steel and have the following advantages:

[0029] (1) Based on traditional low-carbon steel, the present invention adjusts and optimizes microalloying and regulates the microstructure to obtain a structure dominated by single-phase ferrite and supplemented by nano-carbides. The single-phase ferrite steel is strengthened by combining three strengthening methods: carbide dispersion precipitation strengthening, fine grain strengthening and solid solution strengthening, which significantly improves the strength of low-carbon steel and maintains its good plasticity, toughness and formability, and further expands the application range of low-carbon steel;

[0030] (2) The low carbon steel of the present invention controls the content of each element in the composition within a certain range, and maintains a mass ratio of Ti element to Mo element of 1:2, precipitates carbides mainly of (Ti, Mo) C type, and compared with other types of carbides such as TiC, (Ti, Nb) C, etc., (Ti, Mo) C type carbides have high thermal stability, are not easy to grow, maintain nanometer scale, and maximize the strengthening effect;

[0031] (3) The low carbon steel of the present invention controls the Mo element, adjusts the C content, inhibits the formation of pearlite, inhibits the precipitation of carbides in austenite, and forms a structure mainly composed of single-phase alloy ferrite. The alloy elements produce a solid solution strengthening effect in the ferrite matrix, which can increase the strength by 50 to 100 MPa and maintain high toughness and formability.

[0032] (4) The low carbon steel of the present invention precipitates carbides mainly composed of (Ti, Mo) C, and the average diameter of the carbide grains is 5 to 10 nm. The smaller the carbide particles, the more the precipitation amount, the higher the thermal stability, and the carbide grains are dispersed in the ferrite matrix, producing a precipitation strengthening effect, which can increase the strength by 200 to 300 MPa;

[0033] (5) The method of the present invention can refine the austenite grains to the maximum extent through two-stage forging, forming a fine grain strengthening effect, thereby preparing for the subsequent acquisition of fine and uniform ferrite equiaxed grains; at the same time, the process can inhibit the precipitation of large-particle carbides in austenite and promote the precipitation of nanoscale carbides, thereby preparing for the subsequent formation of a large number of dispersed carbides.

[0034] (6) The method of the present invention can obtain uniform and fine equiaxed ferrite grains with an average diameter of 3 to 6 μm. The grains are significantly refined, resulting in a fine grain strengthening effect, which can increase the strength by 150 to 200 MPa.

[0035] (7) The method of the present invention, through composition optimization, process parameter control and microstructure regulation, combined with three strengthening methods, can increase the tensile strength of nano-reinforced high-strength and high-toughness low-carbon steel by 1 to 2 times, while maintaining good toughness, plasticity and formability, and an elongation of 20 to 28%. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1This is a SEM image of the nano-reinforced high-strength and high-toughness low-carbon steel of Example 1 of the present invention.

[0037] Figure 2 This is the TEM image of the nano-reinforced high-strength and high-toughness low-carbon steel of Example 1 of the present invention. DETAILED DESCRIPTION

[0038] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Example 1

[0040] A nano-reinforced high-strength and high-toughness low-carbon steel, comprising the following chemical components in mass percentage: C: 0.06%, Mn: 1.9%, Si: 0.21%, Mo: 0.3%, Ti: 0.15%, Al: 0.07%, and the rest is Fe element, which is obtained by processing a steel ingot obtained by conventional secondary vacuum melting, and the specific preparation process is as follows:

[0041] (1) High temperature homogenization treatment

[0042] The steel ingot is placed in a nitrogen (or argon) protected furnace and heated to 1230°C for 60 minutes.

[0043] (2) Two-stage forging

[0044] Recrystallization zone forging: The ingot sample is taken out from the atmosphere protection furnace for forging, the initial forging temperature is about 1150℃, the final forging temperature is about 960℃, and the forging ratio is 75%;

[0045] Amorphous zone forging: Continue to forge the steel ingot sample, the initial forging temperature is about 930°C, the final forging temperature is about 770°C, and the forging ratio is 50%.

[0046] (3) Staged cooling

[0047] After the two-stage forging is completed, the sample is immediately spray-cooled at a cooling rate of about 30°C / s, and cooling is stopped when the temperature drops to 630°C.

[0048] (4) Short-time isothermal

[0049] After stage-by-stage cooling, the sample was placed in a furnace for heat preservation treatment at a temperature of 620°C for 60 minutes.

[0050] (5) Cooling with the furnace

[0051] The samples after heat preservation are air-cooled in the furnace at a cooling rate of about 0.5-1°C / S. When cooled to below 300°C, they are taken out of the furnace and air-cooled to room temperature to obtain nano-reinforced high-strength and high-toughness low-carbon steel.

[0052] After the above process, the nano-reinforced high-strength and high-toughness low-carbon steel prepared in Example 1 was tested, and the results were as follows:

[0053] The microstructure was observed using a scanning electron microscope (SEM). Figure 1 As shown in the figure, the microstructure is mainly composed of ferrite matrix, the grains are uniform and fine, the grain diameter is 3 to 6 μm, and there is no pearlite structure; the carbide microstructure was observed by transmission electron microscopy (TEM), and the results are as follows Figure 2 As shown, the diameter of the carbide particles is 5 to 10 nm, and there are no large carbide particles.

[0054] Mechanical properties test results: tensile strength R m =908±10MPa, yield strength R e =817±10MPa, elongation A=23.8±1.5%, the strength is significantly improved, and the elongation remains basically stable.

[0055] Example 2

[0056] A nano-reinforced high-strength and high-toughness low-carbon steel, comprising the following chemical components in mass percentage: C: 0.09%, Mn: 2.3%, Si: 0.16%, Mo: 0.2%, Ti: 0.1%, Al: 0.08%, and the rest is Fe element, which is obtained by processing a steel ingot blank obtained by secondary vacuum smelting, and the specific preparation process is as follows:

[0057] (1) High temperature homogenization treatment

[0058] The steel ingot is placed in a nitrogen (or argon) protected furnace and heated to 1200°C for 90 minutes.

[0059] (2) Two-stage forging

[0060] Recrystallization zone forging: The ingot sample is taken out from the atmosphere protection furnace for forging, the initial forging temperature is about 1150℃, the final forging temperature is about 950℃, and the forging ratio is 70%;

[0061] Amorphous zone forging: The steel ingot sample was continued to be forged, with the initial forging temperature being about 930°C, the final forging temperature being about 750°C, and the forging ratio being 40%.

[0062] (3) Staged cooling

[0063] After the two-stage forging is completed, the sample is immediately spray-cooled at a cooling rate of about 30°C / s, and cooling is stopped when the temperature drops to 610°C.

[0064] (4) Short-time isothermal

[0065] After stage-by-stage cooling, the sample was placed in a furnace for heat preservation treatment at a temperature of 600°C for 90 minutes.

[0066] (5) Cooling with the furnace

[0067] The samples after heat preservation are air-cooled in the furnace at a cooling rate of about 0.5-1°C / s. When cooled to below 300°C, they are taken out of the furnace and air-cooled to room temperature.

[0068] After the above process, the mechanical properties of the nano-reinforced high-strength and high-toughness low-carbon steel prepared in Example 2 were tested, and the results were as follows: tensile strength R m =967±10MPa, yield strength R e =853±10MPa, elongation A=18.6±1.5%.

[0069] Example 3

[0070] A nano-reinforced high-strength and high-toughness low-carbon steel, comprising the following chemical components in mass percentage: C: 0.03%, Mn: 1.6%, Si: 0.24%, Mo: 0.35%, Ti: 0.18%, Al: 0.05%, and the rest is Fe element, which is obtained by processing a steel ingot blank obtained by secondary vacuum melting, and the specific preparation process is as follows:

[0071] (1) High temperature homogenization treatment

[0072] The steel ingot is placed in a nitrogen (or argon) protected furnace and heated to 1280°C for 60 minutes.

[0073] (2) Two-stage forging

[0074] Recrystallization zone forging: The steel ingot sample is taken out from the atmosphere protection furnace for forging, the initial forging temperature is about 1200℃, the final forging temperature is about 960℃, and the forging ratio is 80%;

[0075] Amorphous zone forging: Continue to forge the steel ingot sample, the initial forging temperature is about 950°C, the final forging temperature is about 780°C, and the forging ratio is 50%.

[0076] (3) Staged cooling

[0077] After the two-stage forging is completed, the sample is immediately spray-cooled at a cooling rate of about 30°C / s, and cooling is stopped when the temperature drops to 640°C.

[0078] (4) Short-time isothermal

[0079] After stage-by-stage cooling, the sample was placed in a furnace for heat preservation treatment at a temperature of 630°C for 40 minutes.

[0080] (5) Cooling with the furnace

[0081] The samples after heat preservation are air-cooled in the furnace at a cooling rate of about 0.5-1°C / s. When cooled to below 300°C, they are taken out of the furnace and air-cooled to room temperature.

[0082] After the above process, the mechanical properties of the nano-reinforced high-strength and high-toughness low-carbon steel prepared in Example 3 were tested, and the results were as follows: the tensile strength R m =836±10MPa, yield strength R e =742±10MPa, elongation A=26.3±1.5%.

[0083] Example 4

[0084] A nano-reinforced high-strength and high-toughness low-carbon steel, comprising the following chemical components in mass percentage: C: 0.05%, Mn: 2.1%, Si: 0.19%, Mo: 0.4%, Ti: 0.2%, Al: 0.06%, and the rest is Fe element, which is obtained by processing a steel ingot blank obtained by secondary vacuum smelting, and the specific preparation process is as follows:

[0085] (1) High temperature homogenization treatment

[0086] The steel ingot is placed in a nitrogen (or argon) protected furnace and heated to 1250°C for 60 minutes.

[0087] (2) Two-stage forging

[0088] Recrystallization zone forging: The steel ingot sample is taken out from the atmosphere protection furnace for forging, the initial forging temperature is about 1180℃, the final forging temperature is about 940℃, and the forging ratio is 60%;

[0089] Amorphous zone forging: The steel ingot sample was continued to be forged, with the initial forging temperature being about 930°C, the final forging temperature being about 750°C, and the forging ratio being 40%.

[0090] (3) Staged cooling

[0091] After the two-stage forging is completed, the sample is immediately spray-cooled at a cooling rate of about 30°C / s, and cooling is stopped when the temperature drops to 620°C.

[0092] (4) Short-time isothermal

[0093] After stage-by-stage cooling, the sample was placed in a furnace for heat preservation treatment at a temperature of 650°C for 30 minutes.

[0094] (5) Cooling with the furnace

[0095] After heat preservation, the samples are air-cooled in the furnace at a cooling rate of about 0.5-1°C / s. When cooled to below 300°C, they are taken out of the furnace and air-cooled to room temperature.

[0096] After the above process, the mechanical properties of the nano-reinforced high-strength and high-toughness low-carbon steel prepared in Example 4 were tested, and the results were as follows: the tensile strength R m =855±10MPa, yield strength R e =763±10MPa, elongation A=20.7±1.5%.

[0097] Example 5

[0098] A nano-reinforced high-strength and high-toughness low-carbon steel, comprising the following chemical components in mass percentage: C: 0.04%, Mn: 1.5%, Si: 0.15%, Mo: 0.2%, Ti: 0.1%, Al: 0.05%, and the rest is Fe element, which is obtained by processing a steel ingot blank obtained by secondary vacuum melting, and the specific preparation process is as follows:

[0099] (1) High temperature homogenization treatment

[0100] The steel ingot is placed in a nitrogen (or argon) protected furnace and heated to 1220°C for 60 minutes.

[0101] (2) Two-stage forging

[0102] Recrystallization zone forging: The ingot sample is taken out from the atmosphere protection furnace for forging, the initial forging temperature is about 1150℃, the final forging temperature is about 950℃, and the forging ratio is 80%;

[0103] Amorphous zone forging: Continue to forge the ingot sample, the initial forging temperature is about 930°C, the final forging temperature is about 790°C, and the forging ratio is 50%.

[0104] (3) Staged cooling

[0105] After the two-stage forging was completed, the sample was immediately spray-cooled at a cooling rate of about 30°C / s, and cooling was stopped when the temperature dropped to 630°C.

[0106] (4) Short-time isothermal

[0107] After stage cooling, the sample was placed in a furnace for heat preservation treatment at a temperature of 615°C for 90 min.

[0108] (5) Cooling with the furnace

[0109] After heat preservation, the samples are air-cooled in the furnace at a cooling rate of about 0.5 to 1 / s. When cooled to below 300°C, they are taken out of the furnace and air-cooled to room temperature.

[0110] After the above process, the mechanical properties of the nano-reinforced high-strength and high-toughness low-carbon steel prepared in Example 5 were tested, and the results were as follows: the tensile strength R m =834±10MPa, yield strength R e =741±10MPa, elongation A=22.8±1.5%.

[0111] Comparative Example 1

[0112] The chemical composition of Comparative Example 1 is the same as that of Example 1, but the preparation process is different: Comparative Example 1 adopts a traditional annealing process, and does not adopt the "two-stage forging", "stage cooling" and "short-time isothermal" processes of the present invention. The specific process is as follows:

[0113] (1) High temperature homogenization treatment

[0114] The steel ingot is placed in a nitrogen (or argon) protected furnace and heated to 1230°C for 60 minutes.

[0115] (2) High temperature forging

[0116] The steel ingot sample was taken out from the atmosphere protection furnace for forging, the initial forging temperature was about 1150°C, the final forging temperature was about 960°C, and the forging ratio was 75%.

[0117] (3) Air cool to room temperature

[0118] After forging, the samples were air-cooled to room temperature.

[0119] After the above process, the mechanical properties of the material prepared in Comparative Example 1 were tested, and the results were as follows: tensile strength R m =362±10MPa, yield strength R e =283±10MPa, elongation A=26.4±1.5%.

[0120] It can be seen from Comparative Example 1 that the "two-stage forging", "stage cooling" and "short-time isothermal" processes of the present invention were not adopted. Although the elongation was slightly improved (the elongation of low-carbon steel is usually relatively high), the sample was not strengthened by nano-carbide precipitation, and its strength was significantly reduced.

[0121] Comparative Example 2

[0122] The chemical composition of Comparative Example 2 is the same as that of Example 2, and the specific process is also basically the same as that of Example 2, except that: no forging process is performed, and the grain refinement effect of the sample is not obvious.

[0123] The mechanical properties of the material prepared in Comparative Example 2 were tested, and the results were as follows: tensile strength R m =517±10MPa, yield strength R e=432±10MPa, elongation A=24.2±1.5%.

[0124] It can be seen from Comparative Example 2 that the "two-stage forging" of the present invention is not adopted. Although the elongation is slightly improved, the grain refinement effect of the sample is not obvious and its strength is significantly reduced.

[0125] Comparative Example 3

[0126] The chemical composition of Comparative Example 3 is different from that of Example 1 in that: Mo: 0.2%, Ti: 0.2%, and the mass ratio of Mo to Ti is no longer 1:2. The specific process of Comparative Example 3 is the same as that of Example 1.

[0127] The mechanical properties of the material prepared in Comparative Example 3 were tested, and the results were as follows: tensile strength R m =725±10MPa, yield strength R e =637±10MPa, elongation A=17.4±1.5%.

[0128] It can be seen from Comparative Example 3 that when the mass percentage of Mo and Ti elements is not maintained at 1:2, the type of strengthening precipitated carbides is no longer mainly (Ti, Mo) C, large particles of carbides appear in the sample, the precipitation strengthening effect is not obvious, and it is not conducive to the improvement of toughness, plasticity and formability, which ultimately leads to a decrease in both strength and plasticity.

[0129] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A method for preparing nano-reinforced high-strength and high-toughness low-carbon steel, characterized in that: The method comprises the following steps: (1) High temperature homogenization treatment The steel ingot billet after secondary vacuum melting is heated to 1200-1280° C. in an inert gas environment to dissolve all carbides and obtain a uniform single-phase austenite structure; wherein the steel ingot billet contains the following chemical components in mass percentage: C: 0.03-0.1%, Mn: 1.5-2.5%, Si: 0.15-0.25%, Mo: 0.2-0.4%, Ti: 0.1-0.2%, Al: 0.05-0.1%, and the rest is Fe element, and the mass ratio of Mo to Ti is 2:1; (2) Two-stage forging Recrystallization zone forging: The ingot sample is taken out from the atmosphere protection furnace for forging. The initial forging temperature is 1200℃±50 and the final forging temperature is T 再 , T 再 is the recrystallization temperature, ensuring that the forging temperature range is in the austenite recrystallization zone, and the forging ratio is 60-80%, so that the deformed grains are recrystallized to form uniform and fine equiaxed grains and refine the austenite grains; Forging in amorphous zone: Continue forging after forging in recrystallization zone is completed, and the initial forging temperature is T 始 , T 始 T 再 ±30, the final forging temperature is Ar3 temperature, ensuring that the forging temperature range is in the austenite non-crystallization zone, and the forging ratio is 40-60%, so that the grains are not easy to recrystallize, but form dislocation entanglement, promote ferrite nucleation, and inhibit the precipitation of large-particle carbides; (3) Staged cooling After the two-stage forging is completed, the steel ingot sample is spray-cooled at a cooling rate of about 20 to 30°C / s until the temperature drops to 550 to 650°C, and the cooling is stopped; (4) Short-time isothermal After the staged cooling, the steel ingot sample is placed in a furnace for heat preservation treatment at a temperature of 600-650° C. for a time of 30-90 min, so that austenite is transformed into ferrite and nano-scale carbides mainly composed of (Ti, Mo) C are precipitated near the austenite / ferrite grain boundary; (5) Cooling with the furnace After the short-time isothermal treatment, the steel ingot sample is air-cooled in the furnace. When the ingot sample is cooled to below 300° C., it is taken out of the furnace and air-cooled to room temperature to obtain nano-reinforced high-strength and high-toughness low-carbon steel.

2. The method for preparing nano-reinforced high-strength and high-toughness low-carbon steel according to claim 1, characterized in that: The T 再 It is 940~960℃.

3. The method for preparing nano-reinforced high-strength and high-toughness low-carbon steel according to claim 1, characterized in that: In the high temperature homogenization treatment, the heat preservation time is 60 to 90 minutes.

4. The method for preparing nano-reinforced high-strength and high-toughness low-carbon steel according to claim 1, characterized in that: During the non-crystallized zone forging, the Ar3 temperature is 750-800°C.

5. The method for preparing nano-reinforced high-strength and high-toughness low-carbon steel according to claim 1, characterized in that: The staged cooling is performed to reduce the temperature to 600-650° C., and then the cooling is stopped.

6. The method for preparing nano-reinforced high-strength and high-toughness low-carbon steel according to claim 1, characterized in that: The steel ingot contains the following chemical components in mass percentage: C: 0.03-0.09%, Mn: 1.5-2.3%, Si: 0.15-0.24%, Mo: 0.2-0.4%, Ti: 0.1-0.2%, Al: 0.05-0.08%, and the rest is Fe element.

7. A nano-reinforced high-strength and high-toughness low-carbon steel obtained by the preparation method as described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Method for preparing high-strength and high-plasticity ultra-fine grained ferrite and nano-carbide low-carbon steel

    CN101671771A

  • Nanostructure carbide-free bainite medium-carbon alloy steel and preparation method

    CN102321852A